PHYSICOCHEMICAL PROPERTIES AND SENSORY EVALUATION OF JELLY CANDY MADE FROM DIFFERENT RATIO OF k-CARRAGEENAN AND KONJAC - Bagus Sediadi Bandol Utomo; Muhamad Darmawan; Arif Rahman Hakim; Debby T. Ardi (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2014)
A study on quality of jelly candy formulated from k-carrageenan and konjac (jelly powder), hasbeen conducted. The objective of this study was to determine the best ratio of k-carrageenan andkonjac in the formulation of jelly candy. The ratio of k-carrageenan and konjac was varied from40:25; 35:30; 30:35; to 25:40. The quality parameters observed on jelly candy produced were gelstrength, elasticity, stickiness, water activity (a w), and sensory test. Results showed that the bestratio of -carrageenan to konjac was 40:25 (formula A) which produced candy with physicochemicalquality closed to that of commercial one with hardness of 470.7 g, elasticity of 4.5 mm, stickinessof 36.15 g, and a wof 0.5. While the results of the sensory test showed that the difference ratio of -carrageenan and konjac had no significant effect on the product. Based on that result, the bestformulation in production of jelly candy was formula A.